Le multilinguisme dans la Méditerranée antique - ROURE, Réjane (Diglossi@, 2023)
The plurality of languages is a reality that has left its mark on many societies, and which is expressed particularly strongly when different cultures come into contact. Situations of bilingualism or multilingualism are very common in the ancient worlds, provoked in particular by the Greek movements throughout the Mediterranean - in Egypt, Italy, France, Spain - and later by the spread of Latin throughout the provinces of the Roman Empire. This volume brings together articles prepared following a research program of the MSH of Montpellier and a congress held in November 2015. From the Eastern Mediterranean to the West, those papers discuss Egyptian, Phoenician, Greek, Gaulish, Iberian and Latin languages and scripts. The political and economic situations of the different regions studied here - Egypt, Greece, Africa, Italy, Gaul, Spain - are very distinct, and the numerous examples presented show how, through the prisms of multilingualism and onomastics, we can perceive and define the mutual influences of communities in contact.